Do Asset Price Drops Foreshadow Recessions? - Bluedorn, John (IMF Working Papers; Working Paper, 2013)
This paper examines the usefulness of asset prices in predicting recessions in the G-7 countries. It finds that asset price drops are significantly associated with the beginning of a recession in these countries. In particular, the marginal effect of an equity/house price drop on the likelihood of a new recession can be substantial. Equity price drops are, however, larger and are more frequent than house price drops, making them on average more helpful as recession predictors. These findings are robust to the inclusion of the term-spread, uncertainty, and oil prices. Lastly, there is no evidence of significant bias resulting from the rarity of recession starts.